FENOMENA SELEBGRAM ANAK: MEMAHAMI MOTIF ORANG TUA - Afdal Makkuraga Putra; Annisa Febrina (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Nowadays more and more child phenomenon shows up and the phenomenon of children’s personal instagram accounts. This study aims to analyze the motives of parents to upload photos of children on Instagram. This research uses Alfred Schutz’s phenomenology theory with the constructivist paradigm and phenomenology method. To collect data is done by in-depth interviews with 10 informants, and observations of the informants’ instagram accounts. The results of the study and data analysis showed that there were a number of Motives because of uploading photos of children on Instagram that were driven by two things: the experience of photo albums in the past and the disruption and limitations of the technology possessed by parents. While the Motives for (in order to motives) found are related to 3 things. First, it relates to parents’ efforts to make their children known to many people. Second, it relates to a demand to share the moment of child development with others, especially to distant families or friends who have not been met for a long time. Third, as an effort to realize the pride and gratitude of the parents for what they currently have. Based on the motives above, this study categorizes 3 Typics of Parents in uploading photos of children on Instagram, namely Existing Parents, Sharing Parents, and Memories of Parents. This research provides substance in the form of a new model about the type and motivation of parents to upload photos of children on Instagram.